Principali criticità della pedagogia e della didattica dell’emergenza - Isidori, Maria Vittoria (Studi sulla Formazione/Open Journal of Education, 2011)
The author, at the beginning of the essay, presents the specific area of research which is dealing with: a didactics dedicated to educational emergencies. Here are some keywords: humanitarian assistance, disaster, marginalization, spatial and temporal exclusion, extraordinary daily life, etc. We must build a kind of emotional and cognitive habitus to organize our lives in relation to otherness and difference and pedagogy may be a useful tool for the elaboration of experience and of error and to build educational relationships focused on the plurality.